Comparative preclinical evaluation of a polymer-free sirolimus-eluting stent in porcine coronary arteries. (February 2019) - Sperling, Christian; Waliszewski, Matthias W.; Kherad, Behrouz; Krackhardt, Florian
Background: Polymer-free drug-eluting stents (DES) without permanent-polymer coating may be associated with rapid vessel healing, providing a rationale to reduce dual-antiplatelet therapy (DAPT). The aim of the current study was to compare vessel healing of a polymer-free sirolimus-eluting stent (PF-SES), its bare metal stent (BMS) analogue to a permanent polymer-based sirolimus-eluting stent (SES) with proven effectiveness in porcine coronary arteries. Material and methods: An ultrathin-strut cobalt–chromium PF-SES, its BMS analogue and an SES with a permanent polymer were used to study vessel healing and their antistenotic potential. Stents were implanted in porcine coronary arteries for histopathologic analysis at 7, 28 and 180 days. In an additional in vitro study, the thrombogenicity of PF-SES was compared with a fluoropolymer-coated everolimus-eluting stent (EES) which demonstrated low stent thrombosis rates in numerous studies. Results: In the animal study, neointimal growth and injury scores were minimal and inflammation scores were low in the neointima and adventitia in all study groups. After 28 days, neointimal area was lowest in PF-SES when compared with SES and BMS (1.48 ± 0.55 mm² versus 2.43 ± 0.69 mm² versus 1.90 ± 0.85 mm², respectively, p < 0.05) and endothelialization of luminal surfaces was nearly complete in all groups, though SES show the least coverage with occasional adherent luminal inflammatory cells ( p > 0.05). At 180 days, neointimal area and thickness were most pronounced in SES ( p < 0.05) and comparable with BMS implantations, which were characterized by nearly completed vessel healing. PF-SES and BMS had complete endothelialization, absence of fibrin and sustained low inflammatory reaction when compared with the permanent polymer-based SES (inflammation score: PF-SES 0.41 ± 0.74 versus SES 2.52 ± 1.72 versus BMS 0.30 ± 0.65, respectively, p < 0.05 BMS versus SES). Granuloma formation and fibrin accumulation were most pronounced in SES but did not reach statistical significance, p > 0.05). In the in vitro thrombogenicity study, the PF-SES confirmed comparable antithrombogenic properties with regard to the parameters fibrin and platelet binding, and platelet aggregation when compared with the EES. Conclusions: As compared with BMS, the ultrathin-strut cobalt–chromium PF-SES showed similar endothelialization at 28 days and comparable healing characteristics at 180 days efficacious inhibition of neointimal proliferation in porcine coronary arteries with low inflammation responses and a BMS-like endothelialization at 180 days. In addition, in an in vitro model, the PF-SES also confirmed low thrombogenicity as compared with the EES.